(3GdETGQI Edi SjQI GdeUWai hJGQjN ef HYOg ef GdNdaGAs - (3oenZrdWGj Hf nbpdjL Hf YHO Gddg GdHcLQj GdeUQj GdMcQj GdMfaj, CHh YHO Gddg, YdGA GdOjf , J (B762 (3g` s ((3CHh GdaJM (B((3CMO GdYdeGA(B) s)
(3ChdgG (B:s
(3HYO GdHSedg(B: (3HYOMeOGddg GdbgGQ hGdUdGI hGdSdGe Ydi GdeUWai GdeNJGQ GdN s
(3BNQgG (B:s
(3SHjd eGYfO QHi GdMeO ddg GdPi GdYjhf hGddg hGYde s
(3GdfSNI HgG MhGTs
(3GfXQ GdKGfi ef GdJGQjN Qbe (B580s
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs